HPLC Determination of Aflatoxins in Wheat Grains Collected from Central Areas of the Punjab, Pakistan - Ahsan, Sabahat; Ahmad Batti, Ijaz; Hussain, Zaib; Anwar Bukhari, Shazia; Ali Raza Naqvi, Syed; Ali Khan, Zulfiqar; Rafique Asi, Muhammad (Asian Journal of Chemistry, 2013)
Occurrence of aflatoxins (B1, B2, G1 and G2) in samples of wheat from different localities in Faisalabad division, Punjab, Pakistan was determined with latest technique by using HPLC-UV and HPLC-FLD in isocratic mode using MycoSep # 226 columns. Total 40 samples were analyzed each taken from urban, semi-urban and rural areas. Contaminated samples, their percentage, mean value of aflatoxins, highest aflatoxin B1 and total B1 and B2, G1 and G2 was determined. Samples collected from semi-urban areas were found more contaminated 36 μg kg-1 (limit 2-25 μg kg-1 FDA, USA).